(untitled) (International Journal of Nursing Education, 2020)
In recent years, procrastination has become a central issue which is difficult to ignore. It is considered one of the most serious problems in educational settings. So the current study aimed to investigate grit, self-regulation and self-efficacy as predictors of academic procrastination. The study was conducted at the Faculty of Nursing, Zagazig University, Egypt, using descriptive correlational design. A simple random sample of 324 nursing students, were selected from the above-mentioned setting. Four tools were used to collect data for the study; Academic procrastination scale, grit, self-efficacy scale and self-regulation scale. Results revealed highly statistically significant correlations among grit, self-regulation, self-efficacy and academic procrastination where P- value < 0.01, also, grit, self-regulation and self-efficacy were predictors of academic procrastination (R2 = 0.110, R2= 0.290, & R2= 0.659, respectively). It is concluded that grit, self-regulation and self-efficacy can predict academic procrastination. Consequently, it is recommended that faculty should raise nursing students’ awareness about procrastination and provide a training program about self-regulation for them.